2018
DOI: 10.1136/bcr-2017-222155
|View full text |Cite
|
Sign up to set email alerts
|

Management of homozygous familial hypercholesterolaemia in two brothers

Abstract: Homozygous familial hypercholesterolaemia (HoFH) is a rare, genetic disorder of abnormally high levels of low-density lipoprotein cholesterol (LDL-C) requiring aggressive interventions to retard the evolution of atherosclerotic cardiovascular disease. We treated two brothers (ages 46 years and 47 years) with HoFH with statins, lipoproteinapheresis (LA) and the microsomal triglyceride transfer protein inhibitor lomitapide. Both brothers carried the p.Thr434Arg homozygous LDLR mutation and had childhood total ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…This paediatric case series—the first of its kind for lomitapide in HoFH—demonstrates that lomitapide has been effective in reducing LDL-C in paediatric patients with HoFH, and suggests that the drug has a similar adverse event and usage profile to that observed in adult patients. Consistent with real-world data from adult patients [15, 28], this paediatric case series shows a greater reduction in LDL-C at a lower mean dose of lomitapide than in the phase 3 study. This is a curious finding but is replicated across data sets and may be explained by the titration of the dose of lomitapide to desired LDL-C reduction as opposed to the ‘forced’ escalation protocol based on tolerability as used in the phase 3 study.…”
Section: Discussionsupporting
confidence: 86%
“…This paediatric case series—the first of its kind for lomitapide in HoFH—demonstrates that lomitapide has been effective in reducing LDL-C in paediatric patients with HoFH, and suggests that the drug has a similar adverse event and usage profile to that observed in adult patients. Consistent with real-world data from adult patients [15, 28], this paediatric case series shows a greater reduction in LDL-C at a lower mean dose of lomitapide than in the phase 3 study. This is a curious finding but is replicated across data sets and may be explained by the titration of the dose of lomitapide to desired LDL-C reduction as opposed to the ‘forced’ escalation protocol based on tolerability as used in the phase 3 study.…”
Section: Discussionsupporting
confidence: 86%
“…Real et al reported two HoFH brothers (47 and 46 years old) with very premature ASCVD treated with lomitapide over maximum combined LLT and LDL apheresis 32. In the first patient, LDL-C remained close to 130 mg/dL in the interapheresis period.…”
Section: Real-world Clinical Experiencementioning
confidence: 99%
“…The addition of lomitapide powerfully reduced 54% of the LDL-C and 15% of major coronary artery diseases [ 77 ]. Thus, utilizing lomitapide as adjunct therapy can potentially and safely optimize the reduction of LDL-C through genotype-independent effects in FH subjects [ 73 , 79 ].…”
Section: Pharmacogenomics Of Non-statin Lipid-lowering Therapies In Fhmentioning
confidence: 99%